Pengaruh Beban Kerja dan Work-Life Balance terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Mediasi pada Mahasiswa Magister di Jakarta - Stefanus Hendrik Lapian; Osly Usman (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study examines the effect of workload and work-life balance on employee performance through job satisfaction among working master’s students in Jakarta. This population faces dual demands from professional and academic responsibilities, making the maintenance of job satisfaction and performance increasingly challenging. Drawing on the Job Demands-Resources (JD-R) Model and Social Exchange Theory, this study investigates how job demands and resources influence employee outcomes. A quantitative causal approach was employed using data from 57 working master’s students collected through convenience sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The results show that workload negatively and significantly affects job satisfaction but has no significant direct effect on employee performance. In contrast, work-life balance positively and significantly affects both job satisfaction and employee performance. Job satisfaction positively affects employee performance and fully mediates the relationship between workload and employee performance, while partially mediating the relationship between work-life balance and employee performance. These findings support the JD-R Model and Social Exchange Theory by highlighting the role of job satisfaction as a mechanism linking work conditions and employee performance. Practically, organizations and higher education institutions should support work-life balance and manage workload effectively to enhance satisfaction and performance among working postgraduate students.